The impact of exercise intensity and duration for swim training‐induced adaptations in cardiac structure and function in women with mild hypertension - Tórur Sjúrðarson; Nikolai B. Nordsborg; Jacobina Kristiansen; Lars Juel Andersen; Peter Krustrup; Kasper Kyhl; Magni Mohr (Physiological Reports)
Abstract This study aimed to investigate the impact of swim training intensity and duration on cardiac structure and function in mildly hypertensive women. Sixty‐two mildly hypertensive women were randomized to 15 weeks of either (1) high‐intensity swimming (HIS, n = 21), (2) moderate‐intensity swimming (MOD, n = 21) or (3) control (CON, n = 20). Training sessions occurred three times per week. Cardiac measurements were conducted using echocardiography pre‐ and post‐intervention. Both the HIS and MOD groups demonstrated significant within‐group increases in left ventricular mass: 7.3% [1.2; 13.2] (p = 0.02) for HIS and 6.2% [0.5; 11.8] (p = 0.03) for MOD. The MOD group also demonstrated a significant increase in left ventricular internal dimension at end‐diastole by 2.4% [0.2; 4.6] (p = 0.03). Post‐hoc analysis of diastolic function markers revealed reduced mitral valve A velocity in both HIS (−14% [−25; −3], p = 0.02) and MOD (−13% [−23; −3], p = 0.01), leading to increased mitral valve E/A ratios of 27% [10; 47] (p = 0.003) and 22% [5; 40] (p = 0.01), respectively. Additionally, only MOD demonstrated increased left atrial diameter of 4.9% [0.7; 9.1] (p =0.02). A significant time×group effect (p = 0.02) existed for global longitudinal strain, which increased by 1.6% [0.2; 3.0] (p = 0.03) in MOD only. In conclusion, swim training for 15 weeks increased left ventricular mass and improved markers of diastolic function in mildly hypertensive women. These independent of exercise intensity and duration in mildly hypertensive women.